Leucism in Akodon affinis (Allen, 1912) (Rodentia: Cricetidae) - Montoya-Bustamante, Sebastián; Zapata-Mesa, Natalya; Murillo-García, Oscar E. (THERYA, 2017)
Leucism is a condition where animals show a loss of pigments on certain parts of their skin, without affecting soft tissue, a condition that has been poorly reported for Neotropical rodents. Therefore, our goal was to report leucism for Akodon affinis, an endemic species from Colombia, and to analyze the pattern of leucism prevalence in different populations. A. affinis specimens deposited in the Mammals Collection of Universidad del Valle (UV) were examined, and any traces of leucism and its prevalence were recorded for 12 different localities where this species was found. These localities were sampled in different years. The association between incidence of leucism and sex was assessed using a Two-tailed Fisher’s exact test. A total of 11 individuals from five localities displayed traces of leucism in different parts of their body (Table 1, Appendix 1), including cheeks, dorsum and venter (Figure 1). The analysis revealed that the incidence of leucism was higher in males vs. females. Traces of leucism were most frequent in the dorsum than any other part of their body. Although this species is considered as a Least Concern by the International Union for Conservation of Nature (IUCN), these findings suggest that populations of A. affinis might be experiencing inbreeding; however, more information is needed to establish the reproductive and survival consequences of this condition on A. affinis populations.